Virtual Online Home-Based Treatment During the COVID-19 Pandemic for Ultra-Orthodox Young Women With Eating Disorders - Latzer, Yael; Herman, Esther; Ashkenazi, Rahel; Atias, Orna; Laufer, Sofia; Biran Ovadia, Ateret; Oppenheim, Tova; Shimoni, Meirv; Uziel, Moria; Stein, Daniel (Frontiers in Psychiatry, 2021)
Background: With the outbreak of the COVID-19 pandemic, the need arose to maintain treatment continuity for religious Jewish Ultra-Orthodox young women with eating disorders (EDs) previously hospitalized in the ED department at the Ultra-Orthodox “Mayanei Hayeshua” medical center in Israel. This need led to the development of home-based online treatment channels, previously unfamiliar and unaccepted in this population. The implementation of this model had to take into consideration many of the difficulties inherent in the use of online treatment in Jewish Ultra-Orthodox mental health patients. Aims: We sought to investigate our online home-based treatment model implemented during the COVID-19 pandemic in previously hospitalized young Ultra-Orthodox women with EDs. Method: We briefly review the literature on: 1. The Jewish Israeli Ultra-Orthodox culture; 2. Young women in Ultra-Orthodox society; and 3. EDs in Jewish Israeli Ultra-Orthodox women. We then present the inpatient ED department for Ultra-Orthodox young women and describe the online treatment model adapted to this population during the COVID-19 pandemic. We highlight the difficulties, dilemmas, and advantages of our online model with the description of three patients Findings: Online therapy can serve as a barrier to treatment in some cases, due to physical (lack of suitable online devices except phones), familial (over-crowded families), and religious circumstances, as well as because of the patients' reluctance to take part in this treatment. In other cases, virtual home-based treatment can lead to a positive change. This may be the case in patients who find the distancing online model suitable for them, and in parents who are committed to treatment, using their greater physical and emotional presence at home during the COVID-19 pandemic for the good if their ill-daughters. Discussion: This paper highlights the difficulties and possibilities inherent in a virtual home-based treatment during the COVID-19 pandemic for Ultra-Orthodox young women previously hospitalized because of an ED. This model can be effective for some patients and families if undertaken by a multidisciplinary team that is not only knowledgeable about the treatment of EDs and the use of online strategies but also knowledgeable and culturally-sensitive to the specific needs and codes of Ultra-Orthodox populations.